Analysis of the Use of Instagram @Dlhkotajambi as a Campaign Media in Waste Management in Jambi City 2017-2023 - Widya Santoso, Srie Rachma (Journal of Governance and Public Affairs, 2026)
This research aims to analyze the use of Instagram @dlhkotajambi as a campaign medium in waste management in Jambi City. This research uses qualitative methods. The data sources in this study consist of primary and secondary data. Primary data were obtained through in-depth interviews with informants directly involved in managing the social media of the Jambi City Environmental Agency (DLH), as well as through observations of the content uploaded on the Instagram account @dlhkotajambi. Meanwhile, secondary data were obtained from official DLH Jambi City documents, legislation related to waste management, and scientific literature, including books and journals. The findings of this study show that the use of Instagram @dlhkotajambi as a medium for waste management campaigns has been ongoing and demonstrates the commitment of the Jambi City Environmental Agency (DLH) to implementing digital-based public communication. However, the strategy being implemented is still oriented toward information delivery and has not yet fully developed participatory and persuasive approaches that can significantly drive changes in community behavior. Therefore, it is necessary to optimize digital communication strategies through increased interactivity, strengthening community-based collaboration, developing applicable educational content, and innovating in more creative and engaging content packaging.